PENERAPAN MODEL PEMBELAJARAN AIR (AUDITORY, INTELLECTUALLY, REPETITION) UNTUK MENINGKATKAN HASIL BELAJAR SISWA ELEMEN STATIKA BANGUNAN KELAS X DPIB SMK NEGERI 2 BINJAI - Siagian, Yosi Siona; Zulkifli Matondang (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education is a conscious and planned effort to improve the quality of life and human resources, including Vocational High Schools (SMK). Vocational education prepares students to have specific skills tailored to industry needs. However, the learning outcomes of the static calculation of building structures for class X DPIB students at SMK Negeri 2 Binjai are still relatively low. Observations indicated that 65% of students failed to reach the minimum completeness criteria (KKTP). This is largely because the learning model applied is direct instruction, which heavily centers on the teacher as the primary learning source. Consequently, students become passive and struggle to comprehend abstract and highly logical structural concepts. This classroom action research (CAR) aims to apply the AIR (Auditory, Intellectually, Repetition) cooperative learning model to significantly improve student learning outcomes. The research was conducted in two cycles, with each cycle consisting of four essential stages: planning, implementation, observation, and reflection. The subjects of this study were 35 students from class X DPIB. Data collection utilized test instruments, which were validated through validity tests, difficulty index, discriminating power, distractor effectiveness, and reliability testing. The findings revealed a substantial enhancement in cognitive learning outcomes from Cycle I to Cycle II. In Cycle I, the students' average score reached 76.14 with a classical completeness rate of 69%. Following reflective improvements, Cycle II yielded an increased average score of 86.14, with a classical completeness of 91.41%. The 13.10% increase in average scores and the achievement of the >85% classical completeness target demonstrate that the AIR learning model effectively elevates the learning outcomes in building statics computation.